Effectiveness of ceftazidime–avibactam versus colistin in treating carbapenem-resistant Enterobacteriaceae bacteremia. (August 2021) - Hakeam, Hakeam A.; Alsahli, Hala; Albabtain, Lama; Alassaf, Shahad; Al Duhailib, Zainab; Althawadi, Sahar
Highlights: Ceftazidime–avibactam is effective against carbapenem-resistant Enterobacteriaceae (CRE). The efficacy of ceftazidime–avibactam vs. colistin in treating CRE bacteremia was tested. There was a lower risk of mortality with ceftazidime–avibactam vs. colistin in CRE bacteremia. Ceftazidime–avibactam had a higher clinical response vs. colistin in CRE bacteremia. Abstract: Introduction: Antimicrobial treatments for carbapenem-resistant Enterobacteriaceae (CRE) bacteremia are limited, with colistin-based regimens being a primary therapy. Ceftazidime–avibactam is an emerging treatment for various CRE infections. Our study aimed to assess ceftazidime–avibactam effectiveness compared with colistin in patients with CRE bacteremia. Methods: This retrospective, multi-centre study included adult patients with CRE bacteremia treated with ceftazidime–avibactam or colistin, between September 1, 2017 and December 1, 2020, at two tertiary centres in Saudi Arabia. The risk of 14-day mortality was compared between recipients of ceftazidime–avibactam versus colistin, using Cox multivariable regression, adjusted for Pitt score, Charlson index score, and treatment with chemotherapy and immunosuppressive agents. Results: In total, 61 patients were enrolled; 32 received ceftazidime–avibactam, and 29 received colistin. The adjusted risk for 14-day mortality was lower in the ceftazidime–avibactam group than the colistin group (hazard ratio [HR] 0.32; 95% confidence interval [CI] 0.10–0.99; p = 0.049), while the crude 14-day mortality did not differ between the two antibiotics (HR, 0.59; 95% CI 0.21–1.66; p = 0.32). The clinical success rate was higher with the use of ceftazidime–avibactam versus colistin (46.8% versus 20.4%, respectively; p = 0.047). Conclusion: Ceftazidime–avibactam was associated with a lower risk of 14-day mortality than colistin in patients with CRE bacteremia.